Depiction of Environmental Problems in The Novel “Menanam adalah Melawan” by Widodo and its Utilization as Learning Materials in Highschool - Ahmad Abdullah Azzam; Furoidatul Husniah; Sukatman; Inno Cahyaning Tyas (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
Many environmental problems are currently emerging due to human greed, which exploits natural resources excessively without considering the future effects. For example, in the novel Menanam adalah Melawan, which tells of a plan for iron sand mining that threatens thousands of hectares of productive agricultural land in Kulon Progo. This incident ultimately gave birth to characters who reject the discourse that damages the environment. This study aims to describe the depiction of environmental problems in the novel Menanam adalah Melawan using Greg Garrard's ecocritical approach.. This research is a qualitative type using the data analysis method stated by Miles and Huberman. The primary data source in this study is the novel Menanam adalah Melawan by Widodo. The primary data in this study are words, phrases, sentences, and paragraphs that indicate the depiction of the environment in relation to humans. The results of this study reveals environmental ethics, namely respect for nature, the principle of responsibility, cosmic solidarity, the principle of compassion and concern for nature, the principle of not harming, the principle of living simply and in harmony with nature, the principle of democracy, and the principle of moral integrity.. Then, it reveals the forms of environmental damage, divided into several discussions according to Garrard's approach, namely pollution, wilderness, apocalypse, and dwelling. Then, it reveals the impact of environmental damage depicted in the novel Menanam adalah Melawan. Finally, the research findings are distributed to the Indonesian language learning outcomes of Phase F, grade XI, specifically the writing element, within the context of a review text.